All About Shoulder Arthroplasty: What Radiologists Should Know - Chen, Karen C.; Chen, James Y. (Seminars in Musculoskeletal Radiology, 2019)
Over the last decade, the number of shoulder arthroplasty procedures has been increasing and evolving. The types of prostheses have also been evolving, and familiarity with the various design types will assist in postoperative assessment for hardware complications. New preoperative planning tools are available that have radically changed the protocol of preoperative image studies performed. This article reviews the main types of shoulder prostheses, discusses radiologic studies required before surgery, and describes the common complications of shoulder arthroplasty.
Keywords: shoulder arthroplasty; hemiarthroplasty; reverse total shoulder arthroplasty